The influance of discipline and motivation on employee’s work ethics at the office of the Election Supervisory Board (Bawaslu) of Southeast Sulawesi Province - Hamida, La Ode; Bagea, Arfin; Yunus, Asraf (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
This research aims to investigate the impact of discipline and motivation on employees' work ethic at the General Election Supervisory Board (Bawaslu) office in Southeast Sulawesi Province. The research objective is to enhance employees' work ethics at the Bawaslu office in the province of Southeast Sulawesi through discipline and motivation. The study population comprises all General Elections Supervisory Agency office workers in Southeast Sulawesi Province. The sample size was determined to be 65 employees using the probability sampling formula. The research methodology utilized quantitative descriptive and multiple linear regression analysis to analyze the data. The findings reveal that both work discipline and motivation have a significant and positive effect on the work ethic of office employees at the General Election Supervisory Agency (Bawaslu) in Southeast Sulawesi Province, both partially and simultaneously. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.